2012
DOI: 10.1371/journal.pone.0043197
|View full text |Cite
|
Sign up to set email alerts
|

Human Intestinal Dendritic Cells Decrease Cytokine Release against Salmonella Infection in the Presence of Lactobacillus paracasei upon TLR Activation

Abstract: Probiotic bacteria have been shown to modulate immune responses and could have therapeutic effects in allergic and inflammatory disorders. However, little is known about the signalling pathways that are engaged by probiotics. Dendritic cells (DCs) are antigen-presenting cells that are involved in immunity and tolerance. Monocyte-derived dendritic cells (MoDCs) and murine DCs are different from human gut DCs; therefore, in this study, we used human DCs generated from CD34+ progenitor cells (hematopoietic stem c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
70
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 71 publications
(84 citation statements)
references
References 47 publications
13
70
0
1
Order By: Relevance
“…Our observation that L. acidophilus modulates TLR gene expression is in agreement with several studies conducted in Germany, Spain, and France [25,26,29]. …”
Section: Discussionsupporting
confidence: 93%
“…Our observation that L. acidophilus modulates TLR gene expression is in agreement with several studies conducted in Germany, Spain, and France [25,26,29]. …”
Section: Discussionsupporting
confidence: 93%
“…IL-12 also decreased in volunteers that received B. breve CNCM I-4035, whereas the anti-inflammatory index (IL-10/IL-12) increased in the group fed L. paracasei CNCM I-4034. Immunomodulation by these three probiotic strains has been reported in in vitro experiments by Bermudez-Brito et al [32,33]. These authors showed that L. paracasei CNCM I-4034, B. breve CNCM I-4035 and L. rhamnosus CNCM I-4036 inhibited the production of pro-inflammatory cytokines and chemokines by human intestinal dendritic cells challenged with pathogenic bacteria and that such an effect seems to be mediated through a decreased expression of toll-like receptor (TLR)-1, TLR-5 and TLR-9 [32,33].…”
Section: Discussionmentioning
confidence: 99%
“…We speculate that the observed reduction in IL-1β-induced IL-6 secretion in H4 cells after exposure to live L. rhamnosus GG or SpaC may result from modulation of the common TLR and IL-1 receptor signaling pathway. Probiotic lactobacilli have been observed to modulate TLR gene expression and induce the expression of the TLR/IL1R interacting protein TOLLIP and immunoregulatory cytokines in human cord blood-derived dendritic cells (16). We have previously reported that secreted products from probiotic lactobacilli and bifidobacteria down-regulate TLR2 and TLR4 expression and attenuate inflammatory responses through a TOLLIP-dependent mechanism in the immature human gut (17).…”
Section: Discussionmentioning
confidence: 99%